Development of integrated biorefinery model for the production of bioethanol from oil palm frond - Mohd Yusof, Siti Jamilah Hanim (2020)
Application of an efficient pretreatment step is crucial in developing a viable biorefinery system for the production of lignocellulosic bioethanol. Subcritical hydrothermal appears as an economic pretreatment method with high sugar recovery. However, there were limited reports on its application with carbon dioxide (CO2) addition, particularly on oil palm biomass, hence this area should be explored. Moreover, by understanding the mechanism of hemicellulose degradation during pretreatment, the sugar produced hence bioethanol yield could be maximized. Although the integrated biorefinery approach for the production of bioethanol from oil palm frond (OPF) at the oil palm mill was reported promising, assessment of its environmental impact was equally important. Therefore, in this study, subcritical hydrothermal pretreatment of OPF pressed fiber (OPFPF) was conducted using stainless steel tube reactor and miniclave at various temperature, time and CO2 pressure, to evaluate the effect of CO2 addition on glucose production. Similarly, a kinetic study was performed to determine the kinetics of hemicellulose (xylan) degradation during the pretreatment using miniclave. In addition, the environmental and economic viability of integrated biorefinery model for bioethanol production from OPF was assessed by Life Cycle Analysis and cost analysis, each, based on three different case studies. Maximum glucose yield of 57.1% (g/g OPFPF) was obtained with application of tube reactor at 180°C, 1 MPa CO2 for 20 min, and further enhanced to 78.6% using miniclave at similar temperature and pressure for 30 min. Moreover, the rise of temperature and CO2 addition was found to improve the xylan autohydrolysis, with 180°C and 0.5 MPa CO2 as the most suitable condition for high glucose recovery from OPFPF. Furthermore, the integrated biorefinery model for the production of bioethanol from the OPF juice offers the best environmental and economic approach with production cost of $0.25/ L. Based on this study, subcritical hydrothermal pretreatment is a promising method for application at the integrated biorefinery system at the oil palm mill in the future.